2021
DOI: 10.3390/su13041856
|View full text |Cite
|
Sign up to set email alerts
|

For Sustainable Application of Mobile Learning: An Extended UTAUT Model to Examine the Effect of Technical Factors on the Usage of Mobile Devices as a Learning Tool

Abstract: Mobile devices have become an important tool in higher education. Although mobile devices have several benefits for students, the use of these devices is still very limited among students. This low percentage of usage could be attributed to several reasons, both technical and non-technical. Therefore, there is a need to conduct more research in order to understand the necessary factors that would lead to enhanced student usage, thus achieving sustainable mobile learning. In order to achieve that, our study pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 47 publications
9
90
0
6
Order By: Relevance
“…The results show that there is significant relationship between effort expectancy and students' behavioral intention. This is congruent with similar studies [8,11,63], whereas effort expectancy was the most influential determinant of behavioral intention in the context of e-learning [7]. Years of experience have taught us that medical students often show some sort of computer anxiety, especially those who had not previously undergone formal computer courses [82].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results show that there is significant relationship between effort expectancy and students' behavioral intention. This is congruent with similar studies [8,11,63], whereas effort expectancy was the most influential determinant of behavioral intention in the context of e-learning [7]. Years of experience have taught us that medical students often show some sort of computer anxiety, especially those who had not previously undergone formal computer courses [82].…”
Section: Discussionsupporting
confidence: 86%
“…Opposite to the findings of many UTAUT2 based studies [2,[5][6][7][8]12,63], analysis of the first hypothesis that we proposed showed that there is no significant relationship between performance expectancy and students' behavioral intention. Interestingly, our finding was the same as in a study that had a similar focus (using the UTAUT2 model to analyze students' ICT adoption) conducted by Attuquayefio and Addo [13].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Furthermore, this model supports the sustainability of mobile learning by understanding the factors affecting students' intention to use Mlearning before applying this type of education to ensure its success and continuity. It is used to increase the learning motivation among students, enhance students' engagement and increase the sustainability of learning in an effectively way [38].…”
Section: Research Backgroundmentioning
confidence: 99%
“…One of the tremendous improvements relating to communication technology is the development of mobile phones, which are evidence of the rapid change in technological advancements [1]. Remarkable developments in mobile technology and applications have encouraged people to use them in their day-to-day life [2,3]. In recent years, the mobile phone has evolved from essentially an interpersonal communication device to a multimedia machine [4].…”
Section: Introductionmentioning
confidence: 99%